2014
DOI: 10.1002/da.22233
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder Subtypes to Predict Long-Term Course

Abstract: Background Variation in course of major depressive disorder (MDD) is not strongly predicted by existing subtype distinctions. A new subtyping approach is considered here. Methods Two data mining techniques, ensemble recursive partitioning and Lasso generalized linear models (GLMs) followed by k-means cluster analysis, are used to search for subtypes based on index episode symptoms predicting subsequent MDD course in the World Mental Health (WMH) Surveys. The WMH surveys are community surveys in 16 countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 55 publications
(90 reference statements)
2
42
0
2
Order By: Relevance
“…As in the earlier van Loo analysis (van Loo et al ., 2014), inspection of mean percentile scores for solutions in the range between three and eight clusters showed that all solutions defined one class that had the highest mean scores on all outcomes, a second class that had the lowest mean scores on all outcomes, and between one and six other classes that had intermediate mean scores on all outcomes. (Figure 1a–1f) Based on this observation, alternative three-cluster solutions were constructed from the original four-cluster through eight-cluster solutions by collapsing the intermediate clusters in each solution.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…As in the earlier van Loo analysis (van Loo et al ., 2014), inspection of mean percentile scores for solutions in the range between three and eight clusters showed that all solutions defined one class that had the highest mean scores on all outcomes, a second class that had the lowest mean scores on all outcomes, and between one and six other classes that had intermediate mean scores on all outcomes. (Figure 1a–1f) Based on this observation, alternative three-cluster solutions were constructed from the original four-cluster through eight-cluster solutions by collapsing the intermediate clusters in each solution.…”
Section: Resultsmentioning
confidence: 81%
“…(More detailed information on the descriptive characteristics of the sample is presented by van Loo et al . (van Loo et al ., 2014). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A host of studies have documented the important role of anxiety in depressed patients, which predicts reduced treatment efficacy (Fava et al, 2008;Gollan et al, 2012) as well as chronicity of MD, hospitalization, and disability (van Loo et al, 2014). High comorbidity rates between mood and anxiety disorders (Kessler et al, 2005) are well established and traditionally understood as a patients having two distinct diseases.…”
Section: Detailed Discussion Of the Resultsmentioning
confidence: 99%